Detection of ICMPv6-based DDoS attacks using anomaly based intrusion detection system: A comprehensive review - Adnan Hasan Bdair Alghuraibawi; Rosni Abdullah; Selvakumar Manickam; Zaid Abdi Alkareem Alyasseri (Institute of Advanced Engineering and Science, 2021)
Security network systems have been an increasingly important discipline since the implementation of preliminary stages of Internet Protocol version 6 (IPv6) for exploiting by attackers. IPv6 has an improved protocol in terms of security as it brought new functionalities, procedures, i.e., Internet Control Message Protocol version 6 (ICMPv6). The ICMPv6 protocol is considered to be very important and represents the backbone of the IPv6, which is also responsible to send and receive messages in IPv6. However, IPv6 Inherited many attacks from the previous internet protocol version 4 (IPv4) such as distributed denial of service (DDoS) attacks. DDoS is a thorny problem on the internet, being one of the most prominent attacks affecting a network result in tremendous economic damage to individuals as well as organizations. In this paper, an exhaustive evaluation and analysis are conducted anomaly detection DDoS attacks against ICMPv6 messages, in addition, explained anomaly detection types to ICMPv6 DDoS flooding attacks in IPv6 networks. Proposed using feature selection technique based on bio-inspired algorithms for selecting an optimal solution which selects subset to have a positive impact of the detection accuracy ICMPv6 DDoS attack. The review outlines the features and protection constraints of IPv6 intrusion detection systems focusing mainly on DDoS attacks.